2014
DOI: 10.1149/2.0751410jes
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Performance of an Integrated Photoelectrolysis System with 10 × Solar Concentrators

Abstract: Two designs for an integrated photoelectrolysis system that uses a 10× concentrating solar collector have been investigated in detail. The system performance was evaluated using a multi-physics model that accounted for the properties of the tandem photoabsorbers, mass transport, and the electrocatalytic performance of the oxygen-evolution and hydrogen-evolution reactions (OER and HER, respectively). The solar-to-hydrogen (STH) conversion efficiencies and the ohmic losses associated with proton transport in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 34 publications
0
46
2
1
Order By: Relevance
“…The η STH,Avg is 11% or better in Barstow, CA and Albuquerque, NM (locations with good direct-solar resource), and declines in areas with lower direct-solar insolation resource to 9.1% in Quillayute, WA. These values are well below the instantaneous η STH values modeled by Chen et al, 17 where η STH in excess of 25% were reported for a tandem-junction CPEC with no optical losses and a trough-like lens with a CR of 10. It is somewhat problematic to make a comparison between these modeled CPECs, however, as the system modeled in Chen et al 17 will exhibit higher attainable efficiency than that modeled herein due to the higher attainable j SC of the tandem junction PV cells modeled in Chen et al 17 Furthermore, Chen et al 17 do not consider some of the optical losses modeled in this work.…”
Section: Resultscontrasting
confidence: 49%
See 2 more Smart Citations
“…The η STH,Avg is 11% or better in Barstow, CA and Albuquerque, NM (locations with good direct-solar resource), and declines in areas with lower direct-solar insolation resource to 9.1% in Quillayute, WA. These values are well below the instantaneous η STH values modeled by Chen et al, 17 where η STH in excess of 25% were reported for a tandem-junction CPEC with no optical losses and a trough-like lens with a CR of 10. It is somewhat problematic to make a comparison between these modeled CPECs, however, as the system modeled in Chen et al 17 will exhibit higher attainable efficiency than that modeled herein due to the higher attainable j SC of the tandem junction PV cells modeled in Chen et al 17 Furthermore, Chen et al 17 do not consider some of the optical losses modeled in this work.…”
Section: Resultscontrasting
confidence: 49%
“…These values are well below the instantaneous η STH values modeled by Chen et al, 17 where η STH in excess of 25% were reported for a tandem-junction CPEC with no optical losses and a trough-like lens with a CR of 10. It is somewhat problematic to make a comparison between these modeled CPECs, however, as the system modeled in Chen et al 17 will exhibit higher attainable efficiency than that modeled herein due to the higher attainable j SC of the tandem junction PV cells modeled in Chen et al 17 Furthermore, Chen et al 17 do not consider some of the optical losses modeled in this work. The effect of varying direct-solar resource is clearly evident in the SFP of the CPEC modeled herein, because regions with poor resource have a commensurate drop in annual SFP (ranging from 8.8 kg H 2 /m 2 -yr in Barstow, to 2.91 kg H 2 /m 2 -yr in Quillayute).…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…[16][17][18][19][20] We report herein a "one factor at a time" sensitivity analysis [23][24][25] for several types of generic designs of solar-fuels generators. In this study, the sensitivity of the efficiency of the generation of solar fuels to the properties of the various system components was evaluated as a function of the total overpotential of the electrocatalysts for a variety of light absorbers having a range of band gaps and having varying materials quality.…”
Section: -11mentioning
confidence: 99%
“…The voltage losses were not xed relative to the band gap regardless of the actual system operating conditions, 14,44 but instead, as given by eqn (1)- (10), the voltage losses were explicitly a function of the operating voltage and current, in conjunction with the current-dependent ohmicbased voltage losses and kinetically based electrocatalyst overpotential losses, in the specic system being evaluated. The sensitivity analysis investigated herein is applicable to several specic device designs, including a "closed-sandwich" design in which the photocathode and photoanode are assembled back-to-back, 18 an "open-sandwich" design with suitable spectral-splitting in which the photocathode and photoanode are assembled side-by-side, 18 a one-dimensional "trough" design and two-dimensional "bubble-wrap" design for the photoelectrochemical cells coupled to solar concentrators, 16 and a membrane-enclosed, vapor-feed design. 20 The analysis is not applicable to device designs in which the geometric area of the electrolyzing components is signicantly different from that of the light absorbers.…”
Section: à2mentioning
confidence: 99%